1996
DOI: 10.1080/09595239600186111
|View full text |Cite
|
Sign up to set email alerts
|

Training primary health care workers about drugs: a national survey of UK trainers' perceptions towards training

Abstract: Reports have consistently shown that non-specialist drug workers (whose working role is not specifically concentrated on dealing with drug-related issues) are reluctant to work with drug users. A number of explanations have been offered to account for this unwillingness including attitudinal factors, occupational constraints and a lack of motivation to learn about drug-related issues. Previously, it has been shown that training affects commitment to working with substance misusers, although failure to attract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…1993), pharmacists (Sheridan & Barber 1996), and general nursing and maternity ward staff (Carroll 1993). Generic healthcare professionals can also be reluctant to work with drug users because they believe that it is beyond their remit, feel insufficiently skilled, are disillusioned by poor treatment outcomes, or are physically afraid (Greenwood 1992, Albery et al . 1996).…”
Section: Introductionmentioning
confidence: 99%
“…1993), pharmacists (Sheridan & Barber 1996), and general nursing and maternity ward staff (Carroll 1993). Generic healthcare professionals can also be reluctant to work with drug users because they believe that it is beyond their remit, feel insufficiently skilled, are disillusioned by poor treatment outcomes, or are physically afraid (Greenwood 1992, Albery et al . 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Negative attitudes and negative emotional reactions have reported among GPs in primary care settings (Glanz, 1993; Greenwood, 1992; Jacka, Clode, Patterson, & Wyman, 1999; Roche, 1997; Roche, Guary, & Saunders, 1991; Roche, Hotham, & Richmond, 2002; Zweben, 1991), psychiatrists (Tantam, Donmall, Webster, & Strang, 1993), and clinical psychology doctoral students (Mundon, Anderson, & Najavits, 2015). But some studies found that health-care professionals’ attitudes and beliefs can be changed via education (Albery et al., 1996; Alshahrani, 2018; Ballon & Skinner, 2008; Corbin, Gottdiener, Sirikantraporn, Armstrong, & Probber, 2012; Department of Health (UK), 1991; Department of Health, Scottish Office Home and Health Department, Welish Office, 1996; Glass & Strang, 1991; Madson, Bethea, Daniel, & Necaise, 2008; McKim et al., 2014; Olsen & Sharfstein, 2014; Sadow & Ryder, 2008; Sanci et al., 2000; Tang, Wiste, Mao, & Hou, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for negative attitude were attitudinal factors, occupational constraints, and a lack of motivation to learn about drug dependency (Albery et al., 1996) and society’s biased conceptions (Moodley-Kunnie, 1988). Reasons for positive attitude were delivery of preventive services, and more positive beliefs toward prevention, attitudes toward working with the population of interest, and self-perceptions of knowledge and management skills about specific prevention (Boekeloo et al., 1991; Cheng, Dewitt, Savageau, & O’Connor, 1999; Franzgrote, Ellen, Millstein, & Irwin, 1997; Gottlieb, Mullen, & McAlister, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that positive, supportive, non-judgemental interactions with healthcare professionals are critical (Sacks & Keks, 1998). However, healthcare professionals may have negative attitudes to working with patients with alcohol-use disorders (Clay, Allen, & Parran, 2008;Durand, 1994), particularly professionals without specialist training in working with individuals with substance use problems (Albery et al, 1996). Among doctors, including General Practitioners, reported barriers include lack of training, inadequate expertise and time constraints (Durand, 1994;Geirsson, Bendtsen, & Spak, 2005), prejudice against individuals with alcohol-use disorders, and negative perceptions about the potential efficacy of treatment (Carr, 2011).…”
Section: Individual-level Treatment Approachesmentioning
confidence: 99%